Major Factors Affecting the Level of Adoption of Document Management Systems in Zambia’s Higher Institutions of Learning - Simpemba, David; Msendo, Robert; Phiri, Jackson (Zambia ICT Journal, 2023)
The aim of the study was to identify the challenges facing, Zambia’s higher institutions of learning in managing manual documents and to determine whether an electronic Document management Systems (EDMS) could be useful. The study in addition had to determine the levels of adoption prevalent in the institutions among the stakeholders to warrant implementing an Electronic Document Management System or otherwise. A quantitative survey was undertaken at three higher learning institutions covering members of staff and learners in the institutions. A questionnaire was designed to help collect the sample data from the three institutions, which was then analyzed using the SPSS application package. The purpose was to use the Technology Acceptance Model (TAM) [3], to model how users come to accept and use technology, the actual system use is the end point where people use the technology. The TAM Model relies on two primary factors influencing an individual’s intention to use new technology ie perceived usefulness, perceived ease of use , to gauge whether they provide positive indicators to show that there are high levels of perception and expectations to influence positively the dependent variables in the TAM model ie. Attitude, behavioral intention and system use. The study revealed high levels of system adoption perceptions overall, in the institutions, to warrant introducing an EDMS technology. The results revealed a very high perceived usefulness and ease of use across the three institutions of higher learning. The study recommended that an Electronic Document Management System be implemented in these higher institutions of learning.